Infraestructura tecnológica para mejorar la calidad de servicio del Comercial Aguirre. - Espinoza Zúñiga, Nathalia Stephany (2022)
Technology underpins almost every aspect of business today, from the work of employees to processes, goods and services when used correctly and can be harnessed to improve connectivity and increase efficiency and productivity infrastructure is defined as a set of elements for storing corporate data, consisting of hardware and software, including the necessary services to improve the internal management, security and confidential information within the devices office tools. Currently, technological infrastructures are widely used within companies, which is why this case study is carried out so that the commercial Aguirre has a technological proposal to facilitate the needs of its customers. Through the information collected through the interview technique, it was concluded to propose a new infrastructure that allows integrating a more feasible data center in which the staff adapts quickly, it is also intended to add to the firewall to protect the commercial data for and so on. avoid wasting time and provide a better service in an efficient manner.